Modifying the engineering properties of naturally occurring bitumen for sustainable pavement construction - Loto, Roland Tolulope; Busari, Ayobmi; Babalola, Helen; Dada, Oluwatosin (Frontiers in Built Environment, 2025)
This study explores enhancing the engineering properties of naturally occurring bitumen by incorporating plastic waste, aiming for sustainable pavement construction. Key objectives include evaluating the rheological, stability, and microstructural characteristics to determine the optimal plastic content for modification. Experimental investigations involved ductility, flash point, penetration, Marshall stability, and flow tests, alongside scanning electron microscopy (SEM) and response surface analysis. Various polymer waste contents (0%–10%) were blended into bitumen using the wet method. Aggregate properties were analyzed per BS EN 933–1 standards, and the influence of polymer content was modeled to optimize the mix design. Incorporating 7.5% polymer waste significantly enhanced binder properties, improving stability, reducing air voids, and minimizing deformation. SEM revealed densified microstructures with reduced pore sizes. While 7.5% polymer addition optimized resistance to cracking and rutting, increasing content to 10% negatively affected penetration values and void content. Flash and fire points increased, enhancing safety against fire hazards. Response surface analysis confirmed the substantial impact of polymer content on stability, with a robust R-squared value of 0.9275. This study offers a cost-effective approach to utilizing waste plastic as a bitumen modifier, addressing environmental pollution while improving road construction materials, with promising implications for scalable and sustainable infrastructure development.